(untitled) (CIPEEX, 2022)
WITH A VIEW TO INSTITUTING POSSIBLE LIMITS TO FREEDOM OF EXPRESSION, THE PRESENT MATTER CONFRONTS HATE SPEECH AS MANIFESTATIONS AIMED AT STIGMATIZED MINORITIES. IN THE FOREGROUND, THE WORK SOUGHT TO CARRY OUT A STUDY ON THE LIMITS OF FREEDOM OF EXPRESSION, WITHIN LIBERAL PARAMETERS, BEING VERIFIED THAT, AS MUCH AS THE CONSTITUTION GUARANTEES IN ITS LETTER OF LAW THE PROTECTION OF FREEDOM OF EXPRESSION, THERE IS THE PROTECTION OF THE RIGHTS OF WOMEN. PEOPLE WHO SUFFER FROM THE ABUSES PRACTICED IN THE NAME OF FREEDOM OF EXPRESSION AND WHICH JUSTIFIES THE INSERTION OF RESTRICTIONS SUCH AS HATE SPEECH. WITH THIS, EVEN THOUGH FREEDOM OF EXPRESSION IS GUARANTEED AND PROTECTED BY THE FEDERAL CONSTITUTION AS A WAY OF ENSURING THE AUTONOMY OF INDIVIDUALS IN SOCIETY, SO THAT EACH ONE CAN FREELY SAY WHAT IS IN THEIR THOUGHTS, THE SATISFACTION OF INSULTING OTHER PEOPLE THROUGH THE HATRED FOR THE FACT OF THEIR COLOR, ETHNICITY, RACE AND RELIGION, IS NOT SOMETHING PROTECTED BY THE CONSTITUTION. &NBSP;